The General Court in Amazon and Engie: A New Effect-based Approach Aimed at the Endorsement of the 'Vestager Doctrine'? - Guido Bellenghi (European Papers, 2021)
(Series Information) European Papers - A Journal on Law and Integration, 2021 6(2), 1097-1116 | European Forum Insight of 29 October 2021 | (Table of Contents) I. Introduction. - II. The facts of the cases. - III. The annulment of the commission's decision in the Amazon case. - IV. The court dismisses the appeals in the Engie case: The tax rulings granted by Luxembourg to Engie breached EU Law. - V. Applying an effect-based approach to State aid control is not enough to effectively tackle harmful tax competition. - VI. Conclusions. | (Abstract) The rulings of the General Court in the cases of Amazon and Engie (respectively, joined cases T-816/17 and T-318/18 Luxembourg. v Commission ECLI:EU:T:2021:252 and joined cases T-516/18 and T-525/18 Luxembourg v Commission ECLI:EU:T:2021:25) are the last two episodes of the "tax ruling saga". This Insight seeks to examine the potential innovations that these judgements could bring in the context of the application of State aid rules to unfair tax practices. Indeed, this contribution attempts to analyse the impact of the abovementioned rulings on both the notions of "State origin" and "selectivity", as well as the new effect-based approach proposed by the Commission and endorsed by the Court. To do so, both previous relevant cases of the "saga" and the current political context are taken into consideration. The Insight concludes that an outcome-based perspective is not enough to render the "Vestager doctrine" an efficient instrument in the fight against harmful tax competition.